Pulp revascularization using platelet rich plasma autologous or in conjunction with a collagen matrix as a therapeutic possibility for teeth with an open apex necrotic pulp and / or periapical pathology. (2014)
Objective: Describe the use of the Autologous Platelet-Rich Plasma or in combination with a collagen matrix as a potential revascularization therapy in teeth with open apices, necrotic pulp and/or periapical lesion. Methods: A thematic literature searchwas conducted from 2007 to 2013 using electronic means,  databases and journals with high impact on endodontic. Results: Regenerative endodontic is a biological based procedure  designed to replace structures that have been damaged, diseased or absent of the pulpo-dentinal complex. There are three factors that guide and allow for tissue regeneration, mesenchymal stem cells (MSC), which can differentiate themselves and support the continuation of the root development, growth factors (GF), for the induction of cell proliferation and differentiation and finally, a suitable scaffold that provides support and promote cell growth and differentiation. Collagen and platelet-rich plasma (PRP) have been reported as the chosen scaffolds in the regenerative endodontic, it is said that they stimulate the formation of tissue, cell adhesion and organization, thus, improving treatment time and duration. Conclusion: In revascularization procedures, selecting a three-dimensional scaffold or support such as collagen type I or PRP in addition to the induction of periapical tissues, it increases the chances of a successful treatment of endodontic regeneration thanks to the properties that they provide and their molecular interaction.